Time perception impairment following thalamic stroke: A case study. Issue 2 (17th February 2018) - Mole, Joe; Winegardner, Jill; Malley, Donna; Fish, Jessica
ABSTRACT: Impaired time perception is considered to be a relatively unusual and poorly understood consequence of brain injury. This paper presents a case study of altered time perception in JB, a 50-year-old woman who in 2011 had a small thalamic stroke affecting the right anteromedian region. We report on her subjective experience and present results from studies of retrospective timing (i.e., estimating how much time has passed and the clock time) and prospective timing (i.e., producing and reproducing intervals). The results showed that relative to neurologically healthy and brain-injured controls, JB had impaired retrospective timing and impaired prospective time reproduction. However, her prospective time production did not differ significantly from either of the control groups. We interpret this to mean that JB's essential timing functions are intact, and that rather, her time perception impairment stems from a problem in anterograde memory for time intervals. Further, we argue that unlike other cognitive domains, time perception alteration is neither anticipated nor evaluated in most patients, yet these impairments can have a remarkably serious impact on daily life. We encourage further investigation of this topic.